Rapid Fabrication of Ni/NiO@CoFe Layered Double Hydroxide Hierarchical Nanostructures by Femtosecond Laser Ablation and Electrodeposition for Efficient Overall Water Splitting. Issue 12 (30th May 2019) - Wu, Haofei; Yin, Kai; Qi, Weihong; Zhou, Xinfeng; He, Jieting; Li, Jinming; Liu, Yanyu; He, Jun; Gong, Shen; Li, Yejun
Abstract: The development of simple and effective methods for the rapid preparation of electrocatalysts for overall water splitting from earth‐abundant elements is an important and challenging task. A facile and ultrafast two‐step method was developed to prepare a Ni/NiO@CoFe layered double hydroxide hierarchical nanostructure (NCF) within a few minutes by femtosecond laser ablation and electrodeposition. In 1 m KOH solution, the optimized NCF catalysts show a low overpotential of 230 mV for the oxygen evolution reaction (OER) at a current density of 10 mA cm −2 with a low Tafel slope of 34.3 mV dec −1, indicating fast and efficient OER kinetics. Owing to the synergistic effect between NiO and CoFe layered double hydroxide, the hydrogen evolution reaction performance of the NCF was also improved. The synthesized electrocatalysts were further utilized in overall water splitting with a potential of only 1.56 V at a current density of 10 mA cm −2 and excellent durability, better than that of the commercial RuO2 (+)//Pt/C(−) system. The present work provides new insights on the rapid and facile preparation of efficient electrocatalysts for overall water splitting on a large scale. Abstract : Quick and easy ! A hierarchical binder‐free Ni/NiO@CoFe LDH nanostructure was prepared by laser ablation and electrodeposition in several minutes. The material displayed efficient electrocatalytic performance for the hydrogen evolution reaction and oxygen evolution reaction in alkaline solution. The catalyst also exhibited excellent activity and stability for overall water splitting under alkaline conditions.